Expression of the mutated transketolase TKTL1, a molecular marker in gastric cancer - Staiger, Wilko; Coy, Johannes F.; Grobholz, Rainer; Hofheinz, Ralf-Dieter; Lukan, Nadine; Post, Stefan; Schwarzbach, Matthias; Willeke, Frank (Oncology reports, 2006)
The nonoxidative pentose phosphate pathway allows glucose conversion to ribose for DNA or RNA synthesis and glucose degradation to lactate controlled by transketolase enzyme reactions. It has been postulated, that this pathway is of the utmost importance in tumors for the proliferation process. We detected a strong upregulation of the mutated transketolase transcript (TKTL1) in a considerable number of patients with gastric cancer (GC) or cancer of the gastroesophageal junction (GEJ). While only 10.8% of the cancer tissues revealed a significant mRNA upregulation, 36.9% of the cancer tissues demonstrated a protein overexpression. We propose that TKTL1 upregulation is a common phenomenon in GC and cancer of the GEJ leading to an enhanced, oxygen-independent glucose usage which might contribute to a more aggressive tumor growth. Since molecular targeted inhibition of transketolase enzyme reactions suppresses tumor growth and metastasis, TKTL1 could be a relevant target for anti-transketolase therapies in gastric cancer.